Inquiry-Based E-Module with an Ethno-STEM Approach to Develop Sustainable Environmental Literacy Skills - Media Sasmita; Sudarmin Sudarmin; Agung Tri Prasetya; Haniza Hanim binti Mohd Zaim (Jurnal Tadris Kimiya, 2024)
Environmental literacy is one of the keys to support the success of sustainable development goals (SDGs). This research aims to develop an inquiry e-module with an ethno-STEM approach to the concept of volatile aromatic compounds. The research subjects involved 46 students in the chemistry education study program who took the course on organic chemistry of natural substances. Data collection was carried out using an environmental literacy questionnaire covering four domains (knowledge, cognitive skills, attitudes and behavior). The results showed that the validity of e-modules in terms of material and media was 82.5% and 93.25%, respectively, which were categorized as very valid. The results of the environmental literacy test indicate that the average scores for knowledge, attitude, cognitive skills, and behavior were 45.91, 46.46, 51.32, and 53.24. All four domains fall within the high category. The inquiry e-module with an ethno-STEM approach is very suitable for developing environmental literacy skills.